Unausgewogen : Freie Ausstellungsmacher in Köln. - Herzogenrath, Wulf; Jappe, Elisabeth; König, Kasper; Kümmel, Ingo; Molderings, Herbert; Ruhrberg, Karl; Schneckenburger, Manfred; Schneider, Dietmar; Vielhaber, Christiane; Kölnischer Kunstverein, Köln (Köln : Wienand Verlag, 1986)
Altmeyer, Jakob ; Julius ; Bijl, Guillaume ; Hansen, Al ; Yilmaz, Adem ; Geismar, Jarg ; Suppengrün, Elias ; Köllges, Frank ; Hiesl, Angie ; Kirves, Dietmar ; Frisch, Mechtild ; Goller, Bruno ; Graubner, Gotthard ; Hoheisel, Horst ; Lambertin, Theo
biografie
Unausgewogen : Freie Ausstellungsmacher in Köln stellen vor im Kölnischen Kunstverein vom 8. Juni bis 2. Juli 1986
Duits
boek